Angstkonstruktionen Kulturwissenschaftliche Annäherungen an eine Zeitdiagnose - Filatkina, Natalia; Bergmann, Franziska (Sprache und Wissen (SuW), 2021)
In spite of extensive research in the field of cultural studies, the topic of fear has not yet been exhausted, especially considering that not even the semantics of its linguistic devices or the diversity of its linguistic constructions have been satisfactorily explained. This study looks to the present day to examine which media generate fear by which means and manage to assert themselves as an acceptable perspective on social reality.